Microstructure and x-ray microtomographic characterisation of deformation in electrodeposited nickel thin-walled hollow spheres - Li, P; Petrinic, N; Siviour, C (2013)
Nanocrystalline grain sizes in the walls of electrodeposited nickel thin-walled hollow spheres were quantified in FIB-TEM and found to fit a log-normal distribution. Based on the microstructure and nanoindentation properties, reliable material data were determined and related to predict bulk compressive behaviour of the spheres through a finite element model. X-ray microtomography of specimens under compression validates the model, and reveals the 3D deformation/failure mechanisms that dominate macroscopic response of the sphere: multiple buckling and contacts in wall materials. © 2013 Elsevier B.V.